2021
DOI: 10.1089/env.2020.0052
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Flow of Oil and Gas: A Spatial and Temporal Analysis of Environmental Justice in Coastal Louisiana from 1980 to 2010

Abstract: Minority communities in Louisiana have long been at the forefront of the struggle to achieve environmental justice. To date, much of this struggle has focused on communities located in the Mississippi River Chemical Corridor, where rural African American communities have historically been disproportionately impacted by the growth of the petrochemical industry. This research examines the broader oil and gas production chain and shows that minority groups residing in Louisiana's coastal zone have been increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Several SCFs we identified are located in the Louisiana industrial corridor, commonly referred to as 'Cancer Alley' [69,70], where a recent EPA investigation found longstanding racial discrimination in the allowable emissions of toxic air pollutants and consequent adverse impacts to the health of Black residents [71]. The distributive justice issues observed for SCFs are consistent with those observed for other phases of the oil and gas production lifecycle across multiple geographic contexts [68,72]. A recent study reported an association between redlining (racist lending and housing policies) and locations of fossil fuel-based electricity generation plants [73].…”
Section: Lack Of Historical Recordsupporting
confidence: 68%
“…Several SCFs we identified are located in the Louisiana industrial corridor, commonly referred to as 'Cancer Alley' [69,70], where a recent EPA investigation found longstanding racial discrimination in the allowable emissions of toxic air pollutants and consequent adverse impacts to the health of Black residents [71]. The distributive justice issues observed for SCFs are consistent with those observed for other phases of the oil and gas production lifecycle across multiple geographic contexts [68,72]. A recent study reported an association between redlining (racist lending and housing policies) and locations of fossil fuel-based electricity generation plants [73].…”
Section: Lack Of Historical Recordsupporting
confidence: 68%
“…Today, Black and low-income residents in Louisiana disproportionately live near chemical plants and oil refineries [53]. According to the Environmental Protection Agency, residents of northern and southwestern regions face higher exposure to air pollutants (e.g., particle matter (PM)) and risk for respiratory and immunological hazards [105], even though oil refineries are concentrated in southeastern Louisiana [44]. In southeastern Louisiana, an 85-mile stretch of predominately Black parishes between Baton Rouge and New Orleans houses over 150 factories.…”
Section: Structural Racism and Segregationmentioning
confidence: 99%
“…Overall, research from rural Appalachia confirms that easements, safety concerns, and other factors facilitate drastic alteration of communities, transforming rural landscapes into sprawling, industrial settings within a few years (Caretta & McHenry, 2020; Donnelly, 2018). Implications of these changes for rural public health and other societal concerns are still coming into focus, but one emerging theme is that oil and gas infrastructure often exacerbates existing social vulnerability (Blinn et al., 2020; Hemmerling et al., 2021). Together, these examples call into question the idea that midstream pipelines have negligible societal impacts in rural areas simply because populations are less dense than in urban areas.…”
Section: Discussionmentioning
confidence: 99%